2007
DOI: 10.1124/jpet.107.121632
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Priming Enhances Delivery and Efficacy of Nanomedicines

Abstract: We have shown that high epithelial cell density is a major barrier to the distribution of protein-bound drugs in solid tumors, and tumor priming (expansion of interstitial space using an apoptosis-inducing pretreatment) can promote drug delivery. This study evaluated the optimal conditions of paclitaxel tumor priming (time window, particle size) and its effects on the delivery and efficacy of nanomedicines. Paclitaxel tumor priming was applied to mice bearing human xenograft tumors. The kinetics of paclitaxel-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
159
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(177 citation statements)
references
References 27 publications
14
159
3
Order By: Relevance
“…42 Potentiation of doxorubicin toxicity by paclitaxel pretreatment corresponds well to the previous reports. 8,43 While sclareol did not promote doxorubicin accumulation, it increased its toxicity. A synergistic action of sclareol and doxorubicin has been demonstrated with monolayers, 27 and our results support the existence of this synergy using three-dimensional cultures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Potentiation of doxorubicin toxicity by paclitaxel pretreatment corresponds well to the previous reports. 8,43 While sclareol did not promote doxorubicin accumulation, it increased its toxicity. A synergistic action of sclareol and doxorubicin has been demonstrated with monolayers, 27 and our results support the existence of this synergy using three-dimensional cultures.…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies that have reported increased delivery of drug-or siRNAloaded liposomes in spheroids or tumors after paclitaxel pretreatment used oropharyngeal FaDu cells. 19,43 In our study, we used doxorubicin-resistant NCI-ADR-RES cells and this may explain the difference of the penetration of the liposomal doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…As a model for a co-injected drug, a vascular contrast agent comprised of an infrared dye attached to a polyethylene glycol (PEG) molecule (IRDye 800CW-PEG; LI-COR) was used [19]. The mice were injected i.v.…”
Section: Act Enhanced Uptake Of Co-administered Macromolecular Infrarmentioning
confidence: 99%
“…For example, we and others have shown that increased tumor porosity enhanced the vessel surface area and blood perfusion (18,19). These spatial heterogeneities, which affect the hydraulic conductivity and diffusivity and result in spatial-dependent interstitial and transvascular transport were captured in the model by assigning spatialdependent parameter values.…”
Section: Model Development: Overviewmentioning
confidence: 99%